PENINGKATAN NILAI KEPEDULIAN SOSIAL MELALUI MODIFIKASI MODEL PEMBELAJARAN KONSIDERASI PADA MAHASISWA TINGKAT I PROGRAM STUDI PGSD FKIP UNIVERSITAS NUSANTARA PGRI KEDIRI - Soenarko, Bambang; Mujiwati, Endang Sri (Efektor, 2015)
Today, human values ranging ignored, beaten by the thought / action hedonistic and pragmatic, which allows the moral decadence. This condition is necessary steps revamping definitely educational value with an appropriate learning model. Model considerations (Sensitivity consideration models) or models' sensitivity attention "as developed McPhail, a learning model affective that the first stage is called “In other People’s Shoes (if you are in the situation of others)”, with the main aim to develop" more attention "interest and feelings of others. This model is possible to touch the mind and feelings that cause a reaction and encouragement to commit an act of moral (emerging awareness of the sensitivity of attention, concern for others). The study aims to prove the hypothesis that "the use of a modified model of learning considerations gives a better effect on the value of social care in the first year students Program of Study PGSD, compared to the use of traditional learning model". Experimental techniques used to Pretest-posttest Control Group Design, treatment in the form of a modified learning model consideration. Treatment effects in the form of a character value social care, and the data were analyzed by using t-test comparisons. Based on the results of the analysis, obtained to of 14.597 with a significance level of 0.00 then concluded Ho is rejected. Then the hypothesis is proven that "The use of a modified model of learning considerations give better effect to the increase in the value of social concern to students, rather than the traditional learning model".